Analysis of binary aluminium tin products with varying compositions and optimum flowability, tensile strength and hardness - Mohammad Khairol Kamal (Universiti Malaysia Perlis, 2009)
Aluminium tin forms have applications in automobiles and electronic industries. The demand for these materials has been growing at a fast pace from several decades. It is therefore desirable that these materials are produced at a lower production cost and in large quantities. This present investigation deals with preparing aluminium tin from the supplier to make a casting in two different molds which is CO2 sand molding and sand molding. CO2 sand molding use silica sand combine with 7% sodium silicate and CO2 gases throw the mold while sand molding use river sand combine with 5% clay and 4% water. This investigation was two pronged, in the first stage aluminium tin was melt in electric furnace and the melting was done at 550 °C as it was to make sure that resulted in better wettability of aluminium tin particles and reduced entrapment of gases in the cast. The second part of this investigation involved evaluation of microstructure and properties of this aluminium in as cast and heat treated conditions. Mechanical properties, which are of major concern, included tensile strength, yield strength, chemical composition, hardness and flowability. Tensile strength was measured by preparing the tensile specimen of ASTM standards in longitudinal direction using Universal Testing Machine (UTM). The hardness measurements were carried out on micro Vickers’s hardness tester on HV scale. By preparing both mold of flowability pattern the molten metal was pour to the mold and measured how far aluminium tin was flow. Microstructure aspects of the investigation essentially involved observing the aluminium under optical microscope and XRF to see the composition of the aluminium tin particles.